GESTION DES SOUS-PRODUITS INDUSTRIELS ET DEVELOPPEMENT DURABLE : CAS DU PHOSPHOGYPSE DE SFAX (TUNISIE) (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
This study concerns the environmental management of the hosphogypsum piles of Sfax (Tunisia). We propose the use of this phosphogypsum in road construction. After characterization of the materials, and study of his variability during storage, we have determined a formulation of mixing with phosphogypsum and calcareous crushed aggregate and cement to obtain seeked mechanical properties. The environmental study has concerned the gamma radioactivity, the standard test of lixiviation, as the durability in a wet climate as in the Center and the South of Tunisia. Experimental site will have to validate this formulation obtained on this laboratory study.